Scale and sustainability: The impact of a women’s self-help group program on household economic well-being in India - Raghunathan, Kalyani; Kumar, Neha; Gupta, Shivani; Thai, Giang; Scott, Samuel P.; Choudhury, Avijit; Khetan, Madhu; Menon, Purnima; Quisumbing, Agnes R. (Informa UK Limited, 2023)
Microfinance groups are a prominent source of small-scale rural credit in many developing countries. In India, evidence of the impact of the now ubiquitous women-only savings and credit self-help groups (SHGs) on household consumption and asset accumulation is inconclusive and based on small-scale interventions. Further, little is known about the sustainability of impacts at scale. We use panel data on close to 2500 households from five states in India to estimate the impact of SHG membership on household expenditure and asset ownership. Over four years, we find small but significant impacts of SHG membership on household expenditure and livestock ownership. Membership duration has a modest effect, suggesting that initial impacts may taper off as the program scales up, though small sample sizes limit our ability to draw inferences. Accompanying evidence on pathways is compelling; related work shows that SHG participation improves information, empowerment, and access to entitlements. While the direct impacts of SHG membership may not suffice to fill gaps in access to credit faced by the rural poor, impacts along these additional pathways could intensify the benefits of these groups